Development of New Student Admissions Features for the Qaryah Thayyibah Elementary School Website in Purwokerto - Purwati, Yuli; Purnawati, Ely; Najmuddin, Faris Labib; Bafaqih, Mohamad Aqil; Alfazri, Rifa (Sistemasi: Jurnal Sistem Informasi, 2025)
One of the key factors supporting effective school management is the quality of the new student admission (PPDB) process. At Qaryah Thayyibah Elementary School, student registration is still carried out manually by filling out a physical form or through a Google Form link, which is then submitted to the admissions committee along with other administrative requirements. Although the school already has a website, it is currently built on WordPress, and the administrators experience difficulties in managing it. The aim of this study is to optimize the school’s website by redeveloping it using the Laravel framework, incorporating UI/UX design that aligns with the school’s branding and functional needs. Additionally, the study involves developing a dedicated PPDB feature on the new website. The system development follows the Rapid Application Development (RAD) method, which includes the stages of planning, analysis, design, and implementation. The outcomes of this research include an optimized school website built using Laravel and the development of an integrated PPDB feature. The implemented system simplifies report generation by enabling direct integration between the school website and PPDB data processing. Moreover, it offers a more structured data storage system, making data retrieval more efficient and effective.